Dermatofibrosarcoma Protuberans of Male Breast: An Unusual Presentation - Kafil Akhtar; Rana K. Sherwani; Prasenjit Sen Ray (Oman Medical Journal, 2012)
Dermatofibrosarcoma protuberans (DFSP) is a rare tumor which usually presents during early or middle adult life, as erythematous indurated firm subcutaneous nodules. DFSP involving the breast is a rare phenomenon and even rarer in males. We describe a case of a male patient who presented with this tumor in his left breast.